First Trimester Risk Factors of Pregnancy Associated Hypertension in Sanpasitthiprasong Hospital - Kanyanat Chotichavanrattanakun; Piyawadee Wuttikonsammakit; Parinya Chamnan (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Objectives: To determine risk factors in first trimester for development of pregnancy associated hypertension (PAH) at Sanpasitthiprasong Hospital.Materials and Methods: A retrospective cohort study was conducted in pregnant women who attended antenatal care at Sanpasitthiprasong Hospital at 10+0 - 13+6 weeks of gestation and had first trimester Down syndrome screening test from October 2015 to November 2018. A total of 230 medical records of pregnant women were reviewed. Maternal baseline characteristics, ultrasonographic findings, serum biochemical levels, maternal and fetal outcomes were recorded. The association of these factors with development of PAH was examined using logistic regression.Results: Among 230 pregnant women, 26 (11.3%) developed PAH. Factors significantly associated with developing PAH included pregestational diabetes mellitus (PGDM) (odds ratio (OR) 15.02, 95%CI 1.199-188.107; p = 0.036), pre-pregnancy body mass index (pBMI) ≥ 25 kg/m2 (OR 4.06, 95% CI 1.443-11.442; p = 0.008), and mean arterial pressure (MAP) (mmHg) (OR 1.11, 95% CI 1.038-1.178; p = 0.002). Pregnant women with PAH developed more preterm delivery (23.1%vs 8.8%; p = 0.025) and neonatal hypoglycemia than those without (11.5% vs 2.5%; p = 0.017). An equation to predict risk of PAH is shown as follows: PAH score = -12.571 + (1.51 x if pBMI ≥ 25 kg/m2 = 1, pBMI < 25 kg/m2 = 0) + (0.122 x mean MAP mmHg) + (2.616 x if PGDM=1, no PGDM = 0). The probability of developing PAH was 1- (0.88 Exp(PAHscore+2.7734)). Conclusion: Pregestational diabetes mellitus, pBMI ≥ 25 kg/m2, and MAP were independent first trimester risk factors for developing PAH.